The Effect of Competency and Work Experience on Employee Performance at PT. Bank Muamalat Indonesia Tbk. Padang Branch - Wulandari, Septi Yova; Febrian, Andis (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2023)
This research was conducted to find out how much influence competence and work experience variables can have on the performance of employees of PT. Bank Muamalat Indonesia Tbk. Padang branch. The results of his research were found through multiple linear regression tests individually, only the work experience variable had an influence on the performance of employees of PT. Bank Muamalat Indonesia Tbk. Padang branch while individual competency variables do not affect performance. But at the same time these two variables of competence and work experience have a positive and significant effect on the performance of employees of PT. Bank Muamalat Indonesia Tbk. The Padang branch with a determinant coefficient of 77.5%, for another 22.5% is affected by different variables that are not currently examined in this research.